2016
DOI: 10.1038/nm.4177
|View full text |Cite|
|
Sign up to set email alerts
|

Persisting positron emission tomography lesion activity and Mycobacterium tuberculosis mRNA after tuberculosis cure

Abstract: The absence of a gold standard to determine when antibiotics have induced sterilizing cure confounds the development of new approaches to treat pulmonary tuberculosis (PTB). We detected PET-CT imaging response patterns consistent with active disease along with the presence of Mycobacterium tuberculosis mRNA in sputum and bronchoalveolar lavage samples in a substantial proportion of adult, HIV-negative PTB patients after standard 6-month treatment plus one year follow-up, including patients with a durable cure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
260
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(276 citation statements)
references
References 60 publications
(61 reference statements)
16
260
0
Order By: Relevance
“…28 Finally, a recent study that used advanced imaging techniques found that persistent Xpert positivity at end of treatment, even when clinical and microbiological cure was achieved, was a risk factor for TB relapse. 29 In this study, 82% of presumptive TB patients with discordant cultureÀ, Xpertþ results had mucosalivary samples, suggesting that these sample types may be negatively impacting the yield of MGIT culture. If this finding is reproduced in other studies, discordant results might be better explained by inter-and intra-sample variability in sensitivity between culture and Xpert rather than non-viable bacillary populations, as they would be expected to be uniformly present in all samples, regardless of rheological characteristics.…”
Section: Discussionmentioning
confidence: 67%
“…28 Finally, a recent study that used advanced imaging techniques found that persistent Xpert positivity at end of treatment, even when clinical and microbiological cure was achieved, was a risk factor for TB relapse. 29 In this study, 82% of presumptive TB patients with discordant cultureÀ, Xpertþ results had mucosalivary samples, suggesting that these sample types may be negatively impacting the yield of MGIT culture. If this finding is reproduced in other studies, discordant results might be better explained by inter-and intra-sample variability in sensitivity between culture and Xpert rather than non-viable bacillary populations, as they would be expected to be uniformly present in all samples, regardless of rheological characteristics.…”
Section: Discussionmentioning
confidence: 67%
“…A blood-based triage test that allows targeted investigation of individuals with active and sub-clinical TB disease, including asymptomatic individuals at highest risk of progression from latency to disease, could help to shorten the time to treatment start, or even prevent incipient disease before symptoms emerge. [6,7] The vision of a TB blood test to identify high-risk individuals for targeted preventive or curative therapy is within reach.…”
Section: Guest Editorialmentioning
confidence: 99%
“…This could lead to local monotherapy, or to suboptimal drug concentrations in certain regions of lesions, facilitating Mtb persistence and the emergence of genetic drug resistance. Furthermore, the lesions within one individual receiving TB treatment are heterogeneous, with some lesions responding to treatment while others do not decrease in size or activity [369]. These differences have been attributed to differential immune responses at the lesional level, although this is hypothetical.…”
Section: Intrinsic Factors Intrinsic Factors Intrinsic Factors Intrinmentioning
confidence: 99%
“…In line with that, a recent study provided evidence for 'active persisters' in TB patients. Employing 18 FDG-PET-CT scanning to monitor lesion activity during antibiotic treatment, many granulomas were found to abate and resolve, but still one third of patients showed intensified and new lesions [369]. Even if lesions intensified due to killed bacteria triggering local immune responses, the emergence of new lesions is hard to explain if not by ongoing infection.…”
Section: Clinical Implications Of Dormancy and Persistencementioning
confidence: 99%
See 1 more Smart Citation